Challenges and opportunities related to health promotion in community pharmacies: Obstacles and professional perspectives - Real, Juan Pablo (2014)
The community pharmacy is an excellent place to identify those with undiagnosed diseases and refer them to their health professionals for treatment and continuing care. However the process of implementation of campaigns and activities to this end in community pharmacy has been slow and implemented by a pharmaceutical minority. It is crucial understand what are the barriers to participation, in order to design enabling actions to achieve greater adherence of pharmacists in these activities. In order to identify and analyze the elements that hinder the dissemination, implementation and sustainability of pharmaceutical services aimed at the promotion and prevention, in the Argentine community pharmacies, a participatory diagnosis workshop was designed. Although pharmacists stressed that the absence of such professional activities entails a deterioration of pharmacists' image recognition in society, they expressed lack of constancy, economic incentive, specific training in the subject, time and physical space as own barriers to implementation thereof. Pharmacists think that these limitations are generally not taken into account when designing or planning campaigns. The university, must encourage interaction and involvement of different actors (patients, caregivers, family, health professionals) in order to engage them in solving the issues together and that they design activities according to local characteristics, to create actions and benefits that can be sustained in the long term.